Anthropology in Bangladesh: Its emergence in relevance to global contextual - Karim, A.H.M Zehadul (Kamla-Raj Enterprises, 2014)
Anthropology offers a special worldview to study human beings, their community-life and various aspects of the indigenous culture from comparative and holistic perspectives; thus, the discipline produces a useful generalization about people and their way of life. The subject matter of Anthropology is as old as human society itself but its formal emergence as a discipline everywhere has been delayed due to several reasons. As an emerging discipline, Anthropology dates back only two centuries ago when a number of renowned scholars in this field oriented themselves in intensive field-based ethnographic studies on various aspects of culture in the global context. A similar contextualization is also relevant in regard to the emergence and development of the discipline in Bangladesh. Bangladesh possesses a long traditional history and heritage for anthropological research though the institutional recognition of the discipline was delayed due to some administrative and technical problems. During the 1950s, a number of foreign scholars had conducted a few valuable research in the Chittagong Hill Tracts (CHT) regions of the country. At the initial stage, tribal studies did not attract local scholars at that time, though many of the academics for the last two decades and until now have become too fascinated by these tribal issues. During the 1970s and onwards until the 1990s however, Redfield's Mexican model (1930) of village studies had remained a desirable ethnographic strategy in Bangladesh and as part of it, a few valuable village-based ethnographic research on rural communities were produced in the country during this period. This trend of rural research continues until now, as every year, a few village-based ethnographic and academic research on various aspects of rural people are conducted. The institutional development of anthropology saw its emergence when the subject was recognized and included as part of the core course for the postgraduate students pursuing their MPhil and PhDs at the Institute of Bangladesh Studies (IBS) who, as part of their research have always employed participant observation method as the main research approach. The same paradigmatic trend however, has not been found in the academic anthropology in all the universities in Bangladesh; as a few of them has the tendency to disregard the traditional research strategies of Anthropology and instead, they base them towards more Philosophical orientation. With this dichotomous divergence, the paper provides a historical overview of the emergence and expansion of Anthropology in Bangladesh and provides critical explanation in an analytical framework.